Turbomachinery performance analysis - Lewis, R. I. (Arnold ; Wiley, 1996)
This modern overview to performance analysis places aero- and fluid-dynamic treatments, such as cascade and meridional flow analyses, within the broader context of turbomachine performance analysis. For the first time ducted propellers are treated formally within the general family of turbomachines. It also presents a new approach to the use of dimensional analysis which links the overall requirements, such as flow and head, through velocity triangles to blade element loading and related fluid dynamics within a unifying framework linking all aspects of performance analysis for a wide range of turbomachine types. Computer methods are introduced in the main text and a key chapter on axial turbine performance analysis is complemented by the inclusion of 3 major computer programs on an accompanying disc. These enable the user to generate and modify design data through a graphic interface to assess visually the impact on predicted performance and are designed as a Computer Aided Learning Suite for student project work at the professional designer level. Based on the author's many years of teaching at degree level and extensive research experience, this book is a must for all students and professional engineers involved with turbomachinery.